Assessment of surface contact fatigue failure in a spur geared system based on the tribological and vibration parameter analysis. (December 2015) - Amarnath, M.; Lee, Sang-Kwon
Abstract: Gears are one of the most common mechanisms for transmitting power and motion and their usage can be found in numerous applications. Studies on gear teeth contacts have been considered as one of the most complicated applications in tribology. The changes in operating conditions such as increase in temperature, load, reduction in viscosity result decrease in lubricant film thickness and degradation of lubricating oil thereby triggering several types of failures on tooth surfaces viz. pitting, scuffing, micro pitting, scoring, and spalling, these faults influence changes in vibration signals. This paper presents the results of experimental investigations carried out to assess wear in spur gears of single stage spur gear box under fatigue test conditions. The studies considered the lubricant film thickness analysis, wear mechanism studies on gear tooth surfaces, oil degradation analysis using Fourier transform infrared radiation (FTIR) method along with vibration signal analysis. The results provide a good understanding of tribological and vibration parameters as measures for effective assessment of wear in spur gears.